2020
DOI: 10.1002/ctm2.160
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β signaling in liver metastasis

Abstract: The presence of liver metastases drastically worsens the prognosis of cancer patients. The liver is the second most prevalent metastatic site in cancer patients, but systemic therapeutic opportunities that target liver metastases are still limited. To aid the discovery of novel treatment options for metastatic liver disease, we provide insight into the cellular and molecular steps required for liver colonization. For successful colonization in the liver, adaptation of tumor cells and surrounding stroma is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 134 publications
(249 reference statements)
1
27
0
Order By: Relevance
“…Hepatic steatosis can cause extracellular matrix (ECM) remodeling and reorganization, which create a fibrotic niche for CRLM and is important in tumor promotion and growth ( 40 ). Transforming growth factor β (TGF-β), which participants in pathogenesis of hepatic steatosis, is pivotal in maintaining liver homeostasis and have a leading role in CRLM ( 41 ). In addition to TGF-β, other cytokines, such as IL-1, IL-6, and TNF-α, contribute significantly to the pathophysiology of hepatic steatosis through stimulation of hepatic inflammation, and can in turn promote CRLM ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic steatosis can cause extracellular matrix (ECM) remodeling and reorganization, which create a fibrotic niche for CRLM and is important in tumor promotion and growth ( 40 ). Transforming growth factor β (TGF-β), which participants in pathogenesis of hepatic steatosis, is pivotal in maintaining liver homeostasis and have a leading role in CRLM ( 41 ). In addition to TGF-β, other cytokines, such as IL-1, IL-6, and TNF-α, contribute significantly to the pathophysiology of hepatic steatosis through stimulation of hepatic inflammation, and can in turn promote CRLM ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was previously suggested that TGF-β1 can be secreted by hepatocytes and macrophages, in turn activating HSCs ( 40 ). Accumulating evidence indicated that TGF-β1 mainly transduces signals through Smad ( 41 , 42 ). We have also reported that Smad assisted β-catenin transport to the nucleus of HSCs, initiating fibrosis gene expression ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…HSCs are the main sources of ECM, and their activation has been considered as a key event in liver fibrosis ( 40 ). In this process, cytokines released from injured hepatocytes initiates HSC activation ( 41 ). In the present study, hepatocyte-HSC interaction was stimulated using a co-culture system, as previously reported ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of CXCL12 from activated HSCs enhances metastatic colonization by binding to CXCR4 on cancer cells and thereby promoting survival and proliferation (Luker & Luker, 2006 ; Shi et al , 2020 ; Zielińska & Katanaev, 2020 ). Additionally, enhanced extracellular matrix deposition from activated HSCs induces a fibrotic liver environment that enhances metastatic growth (Fig 3C ) (Marvin et al , 2020 ). This fibrosis is a physical barrier to anti‐tumorigenic immune cells (Tsuchida & Friedman, 2017 ).…”
Section: Interaction With Specialized Tissue‐resident Cellsmentioning
confidence: 98%